ANALISIS LOGIKA FUZZY MAMDANI DALAM OPTIMISASI HARGA JUAL JAGUNG - Debora Exaudi Sirait; Binsar Tison Gultom (MES: Journal of Mathematics Education and Science, 2022)
At this time the type of crop that is most often planted is corn because it is a plant that is easier to grow than other secondary crops and the cost is also relatively less and the process is not complicated. The profit from the harvest depends on the selling price and the capital used. So that there is uncertainty in determining the profits of the farmer. Given the uncertainty, it is necessary to optimize the selling price. To optimize the selling price, fuzzy logic can be used. Fuzzy Mamdani is a method that is very flexible and has tolerance for existing data or is usually referred to as secondary data. The data obtained is data collected from Uluan District which is known by the local government in Uluan District. Where the data is data from the community in each village starting for 12 periods of planting corn. By using the Mamdani method, the optimum selling price in the first period of 2012 was Rp. 2,644,-.